Effectively Integrating Technology into the Curriculum - Luscre, Kelly A. (Valdosta State University, 2004)
The purpose of the research was to determine if using a web based management system would assist teachers in increasing their level of technology integration during instruction and curriculum. The web based management system, PICASSO, Portal Integrated Curriculum, Assessment, Student Support Operations) was implemented in Cobb County School District as a way to enhance a teacher's ability to effectively integrate technology into their teaching. pre and post-tests were used to determine the effectiveness of the web based program. Forty-one instructional teachers participated in the study. After taking a pre-test regarding individual teacher technology integration level, the web based program was implemented, and teachers were trained on its use. After using the program for four weeks, a post-test was given to see results. This qualitative study included observations, interviews, and a post-intervention survey. Each participant was trained on PICASSO on several occasions, observed implementing technology units, and interviewed as to their belief regarding the new management system. After full implementation, teachers were given a post-test and results showed a significant increase in teacher levels of technology integration from pretest results. Findings suggest that teachers were using the computers during instruction more effectively and on a more frequent basis. Although teachers believed the program to be beneficial, several stated that it would add more work to their already extensive work load. Most participants saw many benefits to using PICASSO in their instruction planning and teaching strategies. The program provides specific state Quality Core Curriculum and lesson plans to match. The majority of the participants were satisfied with the new program and wanted to receive further training. The results of the study were communicated to the learning community through a regularly scheduled faculty "Rally" meeting with teachers and administrators. This meeting provided documentation that PICASSO is effective in assisting teachers to integrate technology more efficiently. Further training will be provided to the faculty and upgrades will continue to be made to the PICASSO site so that it is up to date and current with new curriculum changes and lesson plans.
Keywords: Web based management system; Technology integration; PICASSO; Educational technology; Teaching--Aids and devices; Computer-assisted instruction